2006
DOI: 10.1890/04-0592
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Process Models For Animal Population Dynamics

Abstract: Hidden process models are a conceptually useful and practical way to simultaneously account for process variation in animal population dynamics and measurement errors in observations and estimates made on the population. Process variation, which can be both demographic and environmental, is modeled by linking a series of stochastic and deterministic subprocesses that characterize processes such as birth, survival, maturation, and movement. Observations of the population can be modeled as functions of true abun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
107
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(108 citation statements)
references
References 20 publications
(26 reference statements)
0
107
0
1
Order By: Relevance
“…Simulations that contained both process and observation error were used to assess the validity of this assumption. We found that the methodology was robust to violations of the assumption of no observation error (see SI Text and Table S1 for details), thus obviating the need for a more sophisticated approach of fitting a model with both types of noise (33,34). Further studies are needed to assess the robustness of our findings to more realistic stochasticity and observation error (36).…”
Section: Methodsmentioning
confidence: 82%
“…Simulations that contained both process and observation error were used to assess the validity of this assumption. We found that the methodology was robust to violations of the assumption of no observation error (see SI Text and Table S1 for details), thus obviating the need for a more sophisticated approach of fitting a model with both types of noise (33,34). Further studies are needed to assess the robustness of our findings to more realistic stochasticity and observation error (36).…”
Section: Methodsmentioning
confidence: 82%
“…The full model could be either empirical, in which case it can be fitted using autoregressive techniques (Forchhammer et al 2002), or it could incorporate detailed population dynamic mechanisms using 'hidden process' modelling (Newman et al 2006), which, by modelling the demographic processes explicitly, allows separation of the different sources of uncertainty. If these hidden processes can be expressed in a linear form, the models can be fitted using classical statistical techniques; more complex, non-linear models will require computer-intensive Bayesian methods (Buckland et al 2007), although these are becoming increasingly available.…”
Section: Knowledge Gapsmentioning
confidence: 99%
“…State-space models have great potential for modelling population time series data and have been generalized to admit a variety of population data types and analyses (Newman et al 2006). The state-space approach has also been proposed as a powerful tool for modelling animal movement data because of its ability to deal simultaneously with potentially large measurement errors and variability in the dynamics of movement (Jonsen et al 2003).…”
Section: Introductionmentioning
confidence: 99%